Analisis Kesulitan Dan Permasalahan Belajar Siswa Sd Dari Berbagai Faktor Internal, Eksternal - Putri Ghani Sukoco; Azahra Syaharani Sukamto; Agne Prasıska Maharani; Sri Suwartini; Elina Dewi Oktaviani (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
This research aims to comprehensively analyze the learning difficulties and problems experienced by primary school students, taking into account a range of internal and external factors, and to propose effective strategies for teachers to overcome them. A library research method was employed by reviewing national journals, articles, and other scientific publications issued between 2018–2024. The results reveal that learning difficulties particularly in mathematics and other core subjects stem from cognitive limitations, underdeveloped fine motor skills, low learning interest and motivation, and mismatched learning styles, as well as external factors such as ineffective teaching methods, less supportive learning environments, unstructured teaching materials, and limited use of learning media. To address these challenges, teachers are encouraged to apply innovative and contextual learning approaches, utilize concrete and interactive media, provide scaffolding and individualized support, and create engaging classroom environments that link learning to students’ real-life experiences. These strategies are expected to enhance students’ motivation, comprehension, and academic achievement at the primary school level.